ANALISIS MINAT PEMBELIAN PIZZA HUT DI ERA NEW NORMAL: TINJAUAN TERHADAP CITRA MEREK, PROMOSI, DAN DISKON HARGA DI KALANGAN KONSUMEN KOTA GROBOGAN - Rizqa Nuzul Ramadhan (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2024)
This study aims to determine whether Perceptions of Brand Image, Promotion and Price Discount have an effect on Interest in Buying Pizza Hut in the Era New Normal. The sample of this study using simple random sampling was used for sample collection techniques with a total sample of 100 respondents. This type of research is quantitative. The data used are primary data and secondary data. Data collection techniques are observation, questionnaires, and literature study. The data analysis technique used multiple linear regression, F test, t test, R2. The results of the F test prove the Perceptions of Brand Image, Promotion and Price Discount simultaneously affects the inters  in buying Pizza Hut  in the new normal era, where the Fcount value is 19,911, the terms of the F test are Fcount > FtabIe (19,911>2,70) with a significant value (0,000<0,05) then from these results Ho is rejected and Ha is accepted, meaning that there is a simultaneous  influence between Brand Image, Promotion and Price Discount for Interest in Buying Pizza Hut in Grobogan City.